2014
DOI: 10.3390/ijerph110302580
|View full text |Cite
|
Sign up to set email alerts
|

Health Recommender Systems: Concepts, Requirements, Technical Basics and Challenges

Abstract: During the last decades huge amounts of data have been collected in clinical databases representing patients' health states (e.g., as laboratory results, treatment plans, medical reports). Hence, digital information available for patient-oriented decision making has increased drastically but is often scattered across different sites. As as solution, personal health record systems (PHRS) are meant to centralize an individual's health data and to allow access for the owner as well as for authorized health profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(103 citation statements)
references
References 58 publications
(66 reference statements)
1
102
0
Order By: Relevance
“…Note too how the prediction accuracy (and profile similarity) for all strategies is better for women than for men, regardless of k. In short, women run more evenly paced (predictable) races [Trubee, 2011;Deaner, 2006]. Our results suggest that this also extends to the matter of predicting a personal best time and recommending a bespoke pacing plan.…”
Section: Prediction Error and Profile Similarity Vs Ksupporting
confidence: 54%
See 2 more Smart Citations
“…Note too how the prediction accuracy (and profile similarity) for all strategies is better for women than for men, regardless of k. In short, women run more evenly paced (predictable) races [Trubee, 2011;Deaner, 2006]. Our results suggest that this also extends to the matter of predicting a personal best time and recommending a bespoke pacing plan.…”
Section: Prediction Error and Profile Similarity Vs Ksupporting
confidence: 54%
“…A key concept is pace, which is measured in minutes per mile/km -the inverse of speed -so that higher values correspond to slower speeds and vice versa [Trubee, 2011;Foster et al, 1994;Deaner, 2006;Haney Jr, 2010]. There are three basic pacing strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the interplay between multiple sources in one comprehensive electronic health records platform may not only improve patient self-management, it can transform the tradition of episodic care to a more continuous, collaborative one supporting decision making, care coordination, and communication between providers and patients [27], [42]. As an unconnected collection of personal health information, the PHR is limited but as an interconnected account with the healthcare system as a whole, it offers a wide array of benefits [43].…”
Section: Sdm Via Phr Opportunitymentioning
confidence: 99%
“…Only 4 articles examined a PHR whose functionality met all four SDM elements and not a single article in the review had a PHR which operated using all SDM-enabled functionality as identified by the PHR functional subcategories. [28] , [29] , [21] , [30] , [23] , [31] , [32] , [33] , [34] , [35] , [5] , [36] , [37] , [38] , [25] 14 reminders [26] , [23] , [31] , [22] , [24] , [27] , [20] , [39] , [34] , [35] , [5] , [36] , [8] , [37] 1 SDM infobutton -initiate and track [28] Options 23 personalized decision support [28] , [29] , [21] , [26] , [23] , [31] , [40] , [22] , [32] , [41] , [27] , [42] , [33] , [20] , [39] , [34] , [35] , …”
Section: Summary: Thematic Analysis -Designmentioning
confidence: 99%